Effect of physical fitness and endurance exercise on indirect biomarkers of recombinant erythropoietin misuse - Abellan, R.; Ventura, R.; Pichini, S.; Palmi, I.; Bellver, M.; Olive, R.; Pacifici, R.; Pascual, J. A.; Zuccaro, P.; Segura, J. (International Journal of Sports Medicine, 2007)
Erythropoietin (EPO) and soluble transferrin receptor (sTfR) in serum have been proposed as indirect biomarkers for the detection of recombinant human EPO (rhEPO) misuse in sport. The purpose of the present study was to investigate the influence of different levels of physical fitness, sport, different training workload during the sport season, and endurance exercise in the concentrations of these serum biomarkers for their application into mathematical models to indirectly detect rhEPO misuse. Serum EPO and sTfR concentrations were measured in 96 elite athletes of various sports along the sport season, in 21 recreational athletes at baseline (non exercising) conditions and in 129 other recreational athletes before and after long-distance races (10 and 21 km). In elite athletes, hemoglobin concentrations and percentage of reticulocytes were also measured, and indirect detection models applied. In recreational athletes, for EPO and sTfR, significant differences were only observed after the 21-km race. In baseline conditions, no differences were observed between recreational and elite athletes for EPO and sTfR. In elite athletes, individual EPO and sTfR concentrations slightly changed over the sport season, with coefficients of variation (CV) of 26.1 % and 9.0 %, respectively. Hemoglobin and reticulocytes were influenced by sport, but their individual variation over the sport season was not physiologically relevant (CV of 3.7 % and 21.3 %, respectively). When applying mathematical models for detection of rhEPO administration, only one elite athlete obtained an individual model score above the established thresholds. Physical fitness, sport and different training workload during the sport season had no substantial effect on serum EPO and sTfR concentrations, except in recreational athletes after a 21-km race. Variations observed in mathematical models to detect EPO administration were mainly due to fluctuation in hemoglobin concentrations, commonly observed in elite athletes.